Always looking up : the adventures of an incurable optimist - Fox, Michael J., 1961- (Hyperion, 2009)
The popular film and television actor evaluates the personal philosophy that has enabled his positive outlook in spite of his battle with degenerative Parkinson's disease, in an uplifting account that considers how he has become a happier and more satisfied person by recognizing the gifts of everyday life.